PROSES PEMBELAJARAN MATEMATIKA PADA ANAK SLOW LEARNERS (LAMBAN BELAJAR) - Fida Rahmantika Hadi (Premiere Educandum : Jurnal Pendidikan Dasar dan Pembelajaran, 2016)
This research is aimed to find out the mathematics learning process in class includes readiness of teacher before learning process, implementation and evaluation and follow up. It was a qualitative research. The subjects were taken by purposive sampling. The subjects of this research were mathematics teacher. Data collection techniques in this research were interviews and observation. Technical validity of the data used is triangulation time. The data analysis technique used was consisted of data reduction, data display, and conclusion. The results of this study were (1) teacher preparedness before learning process are by preparing syllabus, lesson plan (RPP), media and learning resources before the learning process begins. (2) the mathematics learning implementation in class done through three activities: pre activity, whilst activity and post activity (3) in evaluation and follow-up stage, teachers plan follow-up activities in the form of remedial learning, enrichment programs, counseling services for students (4) Factors and constraints experienced from slow learners child is may lose interest in the task and refused to resume the task.